Complementary Split-Ring Resonators for Measuring Dielectric Constants and Loss Tangents - Lee, Chieh-Sen; Yang, Chin-Lung (IEEE microwave and wireless components letters, 2014)
A noninvasive planar complementary split-ring resonator (CSRR) for measuring the dielectric constants and loss tangents of material is presented in this letter. Measurements were developed to extract the complex permittivity of the material under test (MUT) using the equivalent RLC resonator circuit model. This technique enables a single-step measurement of the MUT without the need for machining or reshaping. The method requires calculating only two parameters, the resonant frequency (fr) and the magnitude (dB) response, thus achieving a substantial reduction in cost and computation time. A CSRR sensor operating in the 1.8 to 2.8 GHz band is fabricated and tested for verification. The measurement errors in the dielectric constant were less than 7.6%. An efficient technique of CSRR measuring complex permittivity is experimentally verified.